Basaloid squamous cell carcinoma of the larynx: 16 years of experience at the otorhinolaryngology department of IPO-LFG - Nuno O'Neill Mendes; Daniela Serras; João Seixas; Mafalda Oliveira; José Cabeçadas; Lígia Ferreira; Pedro Montalvão; Miguel Magalhães (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objectives: Identify prognostic factors of basaloid squamous cell carcinoma of the larynx (BSCCL); evaluate survival according to staging, sublocalization and treament.